Can We Fix It? Law, Lawyers and Social Change - Tamara Walsh (Bond Law Review)
Social justice advocates often look to the law to solve complex social problems, but what if the law is not able to live up to this challenge? Even successful legal advocacy can have unintended consequences, and well-intentioned changes to the law sometimes do not accord with the wishes of those they affect. With this in mind, it is important to consider the role of lawyers, and the law, in social change, and to appreciate what can and cannot be achieved through changes to the law and legal systems. Here, I reflect on my own advocacy ‘failures’ and explain what I have learned from them. I conclude that lawyers have an important contribution to make to social change movements, however it is important that they listen to, understand and involve people with lived experience in their advocacy efforts.